Making retail modernisation in developing countries inclusive: a development policy perspective - Tilman Altenburg; Elmar Kulke; Caroline Reeg; Lisa Peterskovsky; Aimée Hampel-Milagrosa (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The diffusion of supermarkets in developing countries has profound implications – not only for existing retail stores and informal vendors but also for millions of producers and intermediary traders in the respective supply chains, and for consumers in these countries. Overall, societies are likely to gain from retail modernisation, given that it implies the use of new technologies and exploitation of economies of scale, and thus results in higher productivity, increased convenience and lower consumer prices. However, the fast roll-out of large foreign retail chains in poor countries with very traditional and low-productivity production and retail structures has the potential to destroy the livelihoods of thousands or even millions who currently earn a decent living through traditional farming or intermediary trading or sales. Moreover, manifold trade-offs need to be taken into account: what benefits certain producer or consumer groups may harm others. Developing countries and their international development partners therefore see the challenge ahead as one of managing this transformation in such a way that the harsh effects of structural change are mitigated and local stakeholders have sufficient time and opportunity to adapt to the new business environment. Ignoring retail modernisation and trying to keep modern retailers out of national markets is neither desirable (because the productivity effects will fail to be realised) nor feasible in the long term (due to the prevailing overall trend towards trade and foreign direct investment liberalisation). Delaying the inevitable adaptation of local retail systems to international best practices may imply higher adaptation costs in the future. The challenge is to proactively shape the way national systems adapt to the global retail revolution. Despite the far-reaching impact of the supermarket revolution, this challenge has so far hardly been debated in development policy circles. This omission is possibly due to the cross-cutting nature of the topic: managing the supermarket revolution concerns agricultural development, urban planning and consumer protection alike, and there is usually no central authority or coordinated system for managing the process. Likewise, only a handful of donor agencies tackle retail modernisation, and those that do mainly focus on the micro level – e.g. by training small farmers rather than assisting in the development of comprehensive strategies. Our study reviews a wide range of policy options. It shows that governments have significant leeway for shaping retail modernisation in an inclusive way. Developing country governments display very different attitudes towards retail modernisation and liberalisation, ranging from unconditional liberalisation to bureaucratic overregulation. We argue in favour of a sequenced approach that, on the one hand, supports productivity development and competition and, on the other, fosters technological learning and applies safeguards for the poor. Working collaboratively with retail corporations is, of course, a key element of such an agenda, but this study also presents a host of additional intervention options. It also highlights the potential contribution of donor agencies, which can bring in international expertise, facilitate dialogue and strategy-building, and encourage pilot projects with corporate partners. Furthermore, it introduces the concept of inclusive business and documents how retail corporations can contribute to host country development and improve their performance and corporate image at the same time.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung